Efektivitas Pelatihan Corporate Life Saving Rules (CLSR) terhadap Tingkat Pengetahuan pada Pekerja di Perusahaan Migas, Bojonegoro, Jawa Timur - Arie Sumarlin; KM Agus Riyanto; Dyan Kunthi Nugrahaeni; Novie Elvinawaty Mauliku; Budiman Budiman (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The oil and gas industry is characterized by capital intensity, advanced technology, and a high level of occupational risk. This study aimed to evaluate the effectiveness of Corporate Life Saving Rules (CLSR) training in improving workers’ knowledge at an oil and gas company located in Bojonegoro, East Java. A quasi-experimental design employing a non-equivalent pretest–posttest control group approach was utilized, involving 78 participants divided into an intervention group (39 individuals) and a control group (39 individuals). Statistical analyses were conducted using paired samples t-tests, independent samples t-tests, N-Gain analysis, and multiple linear regression. The findings revealed a significant increase in knowledge within the intervention group, with mean scores rising from 12.41 to 17.28 (p<0.05), while the control group exhibited no statistically meaningful change. Post-intervention comparisons demonstrated a significant difference between groups (p<0.05). The N-Gain value of 65.05% indicates that CLSR training achieved a moderately effective level of knowledge improvement. Categorically, all participants in the intervention group attained a “good” level of knowledge following the training. Regression analysis identified CLSR training as the primary determinant of knowledge enhancement, whereas age, educational background, and length of employment were not statistically significant predictors (p>0.05). In conclusion, CLSR training is empirically proven to be effective in significantly and consistently improving workers’ knowledge in high-risk industrial environments.